Potential novel plant growth promoting rhizobacteria for bio-organic fertilizer production in the oil palm (Elaeis guineensis Jacq.) in Malaysia - Peng, Shih Hao Tony; Chee, Kheng Hoy; Mohd Saud, Halimi; Yusop, Mohd Rafii; Tan, Geok Hun (Multidisciplinary Digital Publishing Institute, 2023)
The present study aimed to characterize the potential plant growth-promoting rhizobacteria (PGPR) based on biochemical tests based on eight bacterial isolates, and to identify potential PGPR based on the 16S rRNA sequencing molecular method. Eight potential PGPR strains (UPMC1166, UPMC1168, UPMC1254, UPMC1376, UPMC1389, UPMC1393, UPMC703 and UPMC704) isolated from the soils in the oil palm (Elaeis guineensis) estates across Malaysia were selected because of their most PGPR activities. They were screened for nitrogen fixation, phosphate and potassium solubilization, and production of indole-3-acetic acid (IAA). All isolates showed the ability to grow between pH 2 to 9 and survive from 2 to 15% (w/v) of the salt medium. Among the isolated PGPRs, four PGPRs (UPMC1166, UPMC1168, UPMC1254 and UPMC1389) showed the ability to fix nitrogen and had the potential to produce IAA. Furthermore, two PGPRs (UPMC1393 and UPMC1376) demonstrated the ability to solubilize phosphate, while three PGPRs (UPMC703, UPMC704, and UPMC1393) showed the ability to solubilize potassium. Therefore, all the above eight PGPR isolates can benefit the oil palm cultivation industry. The molecular identification based on 16S rRNA gene sequence revealed that UPMC1166 was identified as Bacillus methylotrophicus; UPMC1168 as B. siamensis; UPMC1254 as B. subtilis; UPMC1389 as B. albus; UPMC1376 as Lactobacillus plantarum; UPMC1393 as B. marisflavi; UPMC703 as Burkhoderiaanthina and UPMC704 as B. metallica. These novel strains can be further investigated for their viability and effectiveness for bio-organic fertilizer production and application in the immature stage of oil palm growth.